A real time speech translator application for Android - Ang, Xue Yin (2011)
Singapore is a multiracial and multicultural country with tourist visiting from all around the world. Misunderstandings caused by a language barrier can damage the country’s international reputation. The aim is to create a real time speech translator, designed mainly for tourists who visit Singapore. With this translator, misunderstandings that arise due to communication problems can be reduced, and simultaneously aid in the ease of learning a different language. The translator not only provides translation but also it incorporates the use of Google maps to further enhance the tourist’s experience in Singapore. The translator has the ability to automatically detect the language of the input text and translated it to various languages, focusing on Mandarin. After translation, it will automatically read out the translated word, phrase or sentence without the need to initiate the reading of the translated text. The translation function is done by implementing Google translate, TTS functions in the Android library and the eSpeak speech synthesis engine in the application. Google Maps API was used in the implement the mapping function of the overall application. The mapping used was customised for tourists; it allows users to switch between four views, Map view (default), Satellite view, Street view and Traffic view. Satellite view gives the view of how the area of interest is captured in actual circumstances directly from the satellite, Street view allows the user to go down to street level to see how the infrastructure on the selected street looks like and Traffic view shows the traffic conditions on selected roads so as to help the user to plan his or her journey to avoid traffic jams. Users will also be able to enable or disable the placement markers on certain places of interests in Singapore. Some of the advantages that this project has over some others are that firstly, this project is able to perform Text to Speech translation automatically by pressing one button. Secondly, this application uses both Google maps and Google translate in one application. Thirdly, this application supports 39 languages, out of the 50 languages that Google translate supports. Lastly, the time taken to perform language translation and Text to Speech translation is short.